Rancang Bangun Transmisi Daya Serta Pembuatan Sistem Kemudi Mobil Hemat Energi Tipe Urban Concept - Ardinata, Aljaliil; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Motor vehicles are often used for everyday transportation as well as business tools. The large number of motor vehicles in Indonesia causes excessive air pollution. Air pollution from motor vehicles can cause a greenhouse effect on the world. The price of fuel (Fuel Oil) is also a constraint when prices are soaring, even when the availability of fuel is limited. Based on the problems and needs that have been exposed, Shell Eco Marathon makes the race to create energy-efficient vehicles, whose goal is to reduce the excessive use of fuel. Therefore Urban City Car Vehicles were created for the Shell Eco Marathon aimed at supporting the reduction of excessive fuel use. In making Urban Car For Shell Eco Marathon required a reliable power transmission and steering system, easy in maintenance and easy to find spare part. Therefore in the research discussed the planning and manufacturing power transmission of steering for a car of the Shell Eco Marathon concept. It discussed especially the material, connection, and spare part that would be used. Furthermore, it would be expected to produce a good vehicle.Keyword: City car, material selection and components